MEKANISME POLA SALURAN PEMASARAN PUPUK UREA PT. PUPUK KUJANG (Studi Kasus di Gudang Lini III Kota Serang) - Setiawan, Johan; Novianti, Putri (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2017)
Agriculture sector hold important role in economy development as one of agrarian country. One of industry which role in increasing agrculture development is fertilizer industry. This research purpose is to analyze marketing channel patter which happen in PT. Kujang Cikampek fertilizer (A case in Lini III warehouse Serang City) and analyze channel pattern which the most efficient in marketing at area Lini III warehouse Serang City. This research method is descriptive. Location research determined by purposive is in Lini III warehouse Serang City with consider that in Banten is one of absorbtion area of the biggest product in PT. Kujang fertilizer. Technique take of sample use snowball sampling method. Data analyze method use in this research is marketing channel analyzing, marketing function analyze, structure analyze, marketing channel pattern, and marketing habit also marketing margin analyze. The result of this research shows that there are 2 marketing channel patterns happened in fertilizer selling non-subsidy Urea fertilizer (Nitrea) Banten province area. First channel pattern via Lini III warehouse Serang City – distributor – end consumer. While for marketing channel pattern via Lini III warehouse Serang City – distributor – retailer or stall – end counsumer. The most efficient marketing channel pattern is first because has the shortest marketing chain and the smallest marketing margin.